SCANNING OF STUDENTS’ LEARNING STYLE AT SMA NEGRI 7 LUBUKLINGGAU IN ACADEMIC YEARS 2015/2016 - Agus Triyogo (Bandar Lampung University (UBL), 2016)
This research aims to know students’ learning style in mastery English at SMA Negri 7 Lubuklinggau, the researcher took an observation several students to know type of learning style that can be used by teacher in teaching English in the classroom. The researcher took 18 students as the subject of the research where is representative from the whole of student at SMA Negri 7 Lubuklinggau. The objectives at this research are to know the student in learning style in mastery English and the students’ learning strategies to improve their English proficiency. In this research, the researcher used qualitative research which focuses on naturalistic approach, because the researcher wants to know students’ condition in naturally when they learn English. The result show that from eighteen students that chooses, seven students used kinaesthetic in learning English, six students used Auditory and five students used read and write. the result at this research as an inform to the teachers in teaching especially in English, they must understand the characteristic of their students and use mix strategies in teaching in the classroom, so students will understand all of the material well by their learning style.